Courts in a Transition Economy: Case Disposition and the Quantity-Quality Tradeoff in Bulgaria - Valentina Dimitrova-Grajzl; Peter Grajzl; Atanas Slavov; Katarina Zajc (Center for Economic Studies and ifo Institute (CESifo), 2015)
The lack of effective judiciary in post-socialist countries has been a pervasive concern and successful judicial reform an elusive goal. Yet to date, little empirical research exists on the functioning of courts in the post-socialist world. We draw on a new court-level panel dataset from Bulgaria to study the determinants of court case disposition and to evaluate whether judicial decision-making is subject to a quantity-quality tradeoff. Addressing endogeneity concerns, we find that case disposition in Bulgarian courts is largely driven by demand for court services. The number of serving judges, a key court resource, matters to a limited extent only in a subsample of courts, a result suggesting that judges adjust their productivity based on the number of judges serving at a court. We do not find evidence implying that increasing court productivity would decrease adjudicatory quality. We discuss the policy implications of our findings.
Keywords: P37; K40; D02; 330; courts; post-socialist countries; case disposition; quantity-quality tradeoff